2012
DOI: 10.1097/dad.0b013e31824fec43
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Intravascular Anaplastic Large T-Cell Lymphoma

Abstract: Intravascular lymphoma (IVL) is a rare subtype of extranodal lymphoma. In the 2008 WHO classification of tumors of the hematopoietic and lymphoid tissues intravascular large B-cell lymphoma is included as a distinct entity. IVL of T-cell type is not included as a diagnostic category and is only mentioned in passing by Nakamura et al. as "a different entity" in their discussion of intravascular large B-cell lymphoma. T-cell IVL is rare, the majority of cases being of natural killer/T-cell phenotype. Exceptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…However, the follicular lymphoma was not identified in the initial bone marrow biopsy despite a retrospective review of the cervical LN biopsy slides obtained 3 years before and showed diagnostic features of a follicular small cleaved cell lymphoma. [41][42][43][44][45][46] The median age of the reported patients is 56 (age, 33-86) years, with a male-to-female ratio of 5:4. When she returned 3 years later, she was found to have worsening symptoms, including more prominent skin nodules with liver involvement.…”
Section: Discussionmentioning
confidence: 99%
“…However, the follicular lymphoma was not identified in the initial bone marrow biopsy despite a retrospective review of the cervical LN biopsy slides obtained 3 years before and showed diagnostic features of a follicular small cleaved cell lymphoma. [41][42][43][44][45][46] The median age of the reported patients is 56 (age, 33-86) years, with a male-to-female ratio of 5:4. When she returned 3 years later, she was found to have worsening symptoms, including more prominent skin nodules with liver involvement.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly defined as a rare subtype of extra-nodular DLBCL [11,12]; however, recent reports have demonstrated IVL with natural killer cells or T-cell lymphomas [44,45].…”
Section: Ivl Frequencymentioning
confidence: 99%
“…A rare T-cell and NK cell variant of intravascular lymphomas has been described and is associated in some cases with EBV. 122 Iacobelli and colleagues 123 reported a case of intravascular ALCL restricted to the skin. The T-cell and NK-cell variant is not included as a distinct entity or subtype in the current WHO classification.…”
Section: Intravascular Large B-cell Lymphomamentioning
confidence: 98%